Factors that affecting purchase intention towards skincare products. A study of students in Universiti Teknologi Mara (UiTM) Kampus Bandaraya Melaka, Malaysia / Siti Najihah Rosman - Rosman, Siti Najihah (Faculty of Business and Management, 2018)
The research conducted is to explore the factors affecting purchase intention of skincare brands: A study of students in Universiti Teknologi Mara (UiTM) Kampus Bandaraya Melaka, Malaysia. This study will begin with the research background, problem statement, following by objective of the research, research questions, hypothesis, and significance of the study.